Synergies between L1 and L2 and their Practical Implications for the EFL Classroom (Pädagogische Horizonte, 2017)
The present article seeks to establish synergies between L1 and L2 acquisition and, thus, has practical implications for the EFL classroom. Carefully juxtaposing insights that have been gained through L1 and L2 research will further yield sufficient evidence that explicit grammar teaching has to be very critically reviewed, as it is simply not done in L1 acquisition – one fact, amongst a great many others, that may explain why L1 acquisition is invariably more successful than L2 acquisition. Finally, as interaction and positive feedback seem to be at the core of the matter, some practical hints will be given as to how to simulate successful L1 conditions in L2 classrooms by using interactive games and activities that help to boost the learners’ confidence and, in the long run, their fluency and speaking skills.
Keywords: independent grammar systems; morpheme studies; natural order of acquisition; academic style; practical implications; L1 and L2 acquisition theories